Review System Geodetic Reference In Some Countries - Heri Andreas; Dina A. Sarsito; Irwan Meilano (Indonesian Journal of Geospatial, 2013)
Abstract. Two important things in the scope of Geodesy and Geomatics engineering and geodetic science is positioning and coordinates. The position is defined simply as the existence of an object to other objects , while the coordinate is defined as a position statement quantitatively , or others mentioned in the definition of the coordinates is a quantity (numerical) to declare the location or position of a point (object) in a chamber (field) . To ensure consistency and standardization of a coordinate , which applies to the local system to the global (world) , it is necessary to declare the existence of a coordinate system . This system is called the coordinates reference system or Geodetic Reference System , with elements of a constituent or parameter consist of Reference Frame and coordinates Reference System on the earth's static system , and the reference system , coordinates and Datum Reference Frame coordinates on the earth's dynamic systems . Datum Coordinates further divided into several types of Datum Static, Semi Dynamic , Dynamic , Semi Kinematic and Kinematic .What Geodetic Reference System which is generally used in the global scope ( the world ) will be discussed in this paper . Hope this theme can be one basis when we as a community of Geodesy and Geomatics , or even national community select or determine what the true Geodetic Reference System . This paper will also discuss specifically Geodetic Reference System in several countries . Keywords : Positioning, Coordinate, Geodetic Reference System, Coordinate Datum